Haplotyping the human T-cell receptor beta-chain gene complex by use of restriction fragment length polymorphisms. - Charmley, P (1990)
We have studied the genetic segregation of human T-cell receptor beta-chain (TCR beta) genes on chromosome 7q in 40 CEPH (Centre d'Etude du Polymorphisme Humain) families by using restriction fragment length polymorphisms (RFLPs). We constructed haplotypes from eight RFLPs by using variable- and constant-region cDNA probes, which detect polymorphisms that span more than 600 kilobases of the TCR beta gene complex. Analysis of allele distributions between TCR beta genes revealed significant linkage disequilibrium between only 6 of the 28 different pairs of RFLPs. This linkage disequillibrium strongly influences the most efficient order to proceed for typing of these RFLPs in order to achieve maximum genetic informativeness, which in this study revealed a 97.3% level of heterozygosity within the TCR beta gene complex. Our results should provide new insight into recent reports of disease associations with the TCR beta gene complex and should assist in designing future experiments to detect or confirm the existence of disease-susceptibility loci in this region of the human genome.